(untitled) (Indonesian Art and Justice Review, 2025)
In Indonesia, corruption remains a pervasive issue, and artists have often been at the forefront of social and political commentary, using their work to critique the state of governance. This paper explores how Indonesian artists employ satire and humor in their art to challenge government corruption, societal injustices, and political inequities. By examining the techniques, themes, and political messages in satirical works, this study delves into the ethical and legal ramifications of using art as a tool for political critique. The paper also assesses how this form of art contributes to wider conversations on justice, transparency, and accountability in Indonesia, while considering the risks that artists face in expressing dissent in a politically sensitive environment.